2000
DOI: 10.1038/sj.bmt.1702535
|View full text |Cite
|
Sign up to set email alerts
|

Utility of obtaining blood cultures in febrile neutropenic patients undergoing bone marrow transplantation

Abstract: Summary:Infection remains an important cause of morbidity and mortality after bone marrow or stem cell transplantation. To evaluate the role of obtaining blood cultures for intermittent or persistent fever in neutropenic patients on antibiotic therapy, we performed a retrospective chart review of 196 consecutive patients admitted to the Bone Marrow Transplant Unit at the University of North Carolina Hospitals from 1995 to 1998. From the cohort of 196 patients, 154 patients developed neutropenic fever. The init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
1
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 28 publications
(20 reference statements)
3
44
1
2
Order By: Relevance
“…The situation is different for persistent fever during antibiotic therapy and for diagnosis of IFI which may otherwise not be detected by blood cultures. In the setting of persistent fever during antibiotic therapy, the role for blood cultures is very small, since several studies show that a new pathogen is detected in Ͻ1% of cases (4,15). Our study confirms this finding as we also had only one patient with a newly positive result after the start of antimicrobial therapy.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The situation is different for persistent fever during antibiotic therapy and for diagnosis of IFI which may otherwise not be detected by blood cultures. In the setting of persistent fever during antibiotic therapy, the role for blood cultures is very small, since several studies show that a new pathogen is detected in Ͻ1% of cases (4,15). Our study confirms this finding as we also had only one patient with a newly positive result after the start of antimicrobial therapy.…”
Section: Discussionsupporting
confidence: 79%
“…While systemic infection is the most common cause of a febrile neutropenia episode (FNE) with significant effects on morbidity and mortality, only 30% of blood cultures taken at the onset of fever are positive (11,15). Nonetheless, patients with FNEs are treated with broad-spectrum antimicrobial agents regardless of the result of their blood culture (7) because potentially life-threatening infections need early treatment to ensure better clinical outcome.…”
mentioning
confidence: 99%
“…Blood culture rarely isolates causative organisms after initiation of antibiotic therapy. 15,25 Antibiotics decrease the yield of blood cultures, and routine collection of blood samples may not be helpful in allo-SCT recipients. However, our study revealed a high incidence of 'occult' BSI in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…1,[9][10][11][12] Although blood culture is the standard method for obtaining a definitive diagnosis of bacteremia, the usefulness of surveillance blood culture has not been adequately evaluated in patients who are on antibiotic prophylaxis. [13][14][15] Serody et al 15 found that blood culture failed to isolate causative organisms in patients developing neutropenic fever while on prophylactic antibiotics. Furthermore, in allo-SCT recipients, inflammatory reactions are frequently absent during neutropenia, and are easily masked by immunosuppressive agents, particularly corticosteroids.…”
mentioning
confidence: 99%
“…[4][5][6][7][8][23][24][25][26] Our study shows that routine surveillance cultures can predict the etiology of a bacteremia in 50% of cases. For coagulase-negative staphylococci, the predictive value of such cultures is, in fact, quite low because of the very high rate of colonization observed in our patients (77%).…”
Section: 11mentioning
confidence: 99%